Reading first and beyond : the complete guide for teachers and literacy coaches - Block, Cathy Collins. 4 0 16; Israel, Susan E.; 5 (Thousand Oaks, CA : Corwin Press, 2005)
A guide for teachers and literacy coaches that describes the provisions and requirements of the Reading First Legislation and the No Child Left Behind federal programs, including strategies to differentiate for special learners.
Includes bibliographical references and index.
Professional.
Keywords: 2 -- 0; 6; Study and teaching (Primary) -- Reading (Primary);Reading comprehension;Action research in education -- United States.;United States.;United States. -- 20; 20; 2